PELATIHAN KOMUNIKASI EFEKTIF DAN MANAJEMEN KONFLIK UNTUK PEMBERDAYAAN SDM ORKI (OLAHRAGA KEBUGARAN INDONESIA) KOTA TANGERANG SELATAN - Aprilia Astuti; Yeni Liana Sari; Denies Susanto (Abdi Jurnal Publikasi, 2026)
Organic waste remains a significant environmental issue in urban areas, including South Tangerang City. Low public awareness and skills in managing organic waste have led to an increase in the volume of waste ending up in landfills (TPA). This Community Service activity aims to provide education and understanding to members of the South Tangerang City Nusantara Gymnastics Community (KSN) regarding organic waste management based on a circular economy. The methods used included education, interactive discussions, and simple organic waste processing practices. The results of the activity demonstrated an increase in participants' knowledge and awareness regarding the importance of organic waste management and the potential economic value it can generate. This activity is expected to encourage changes in community behavior towards sustainable waste management.